Molecular characterization and detection of 16SrIII group phytoplasma associated with huanglongbing symptoms - Wulff, Nelson Arno [UNESP]; Fassini, Camila Giacomo; Marques, Viviani Vieira; Martins, Elaine Cristina; Coletti, Daniela Aparecida Bononi; Teixeira, Diva do Carmo; Sanches, Marcio Martinello; Bové, Joseph Marie (Scientific Societies, 2019)
When huanglongbing (HLB) was found in Brazil in 2004, ‘Candidatus Liberibacter americanus’ was infecting most of the trees while ‘Ca. L. asiaticus’ was present in a minor proportion. Currently, ‘Ca. L. asiaticus’ is the predominant bacterium associated with HLB in citrus trees in São Paulo (SP) and Minas Gerais (MG) States, the major citrus-growing regions in Brazil. A phytoplasma from the 16SrIX group was associated with HLB symptoms in Brazil in 2007, in plants free of Liberibacter spp. In this report, HLB samples testing negative for ‘Ca. L. asiaticus’, ‘Ca. L. americanus’, and 16SrIX phytoplasma were infected with 16SrIII phytoplasmas. Coinfection with ‘Ca. L. asiaticus’ and 16SrIII was also found. The 16S ribosomal RNA (rRNA) gene sequences from 22 samples were obtained and sequenced, confirming that the 16SrIII group phytoplasma is associated with HLB symptoms in SP and MG States. Ten single-nucleotide polymorphisms (SNPs) were found in the 1,427-bp 16S rRNA gene sequences from 16SrIII phytoplasmas from citrus, whereas none was detected in 16S rRNA gene sequences among 16SrIX phytoplasma from citrus. Ribosomal protein (rp) rpsSrplVrpsC gene sequences were amplified with 16SrIII group-specific primers, sequenced from a subset of nine samples, and assembled into three groups based on eight SNPs. SNPs in 16S rRNA gene and rp gene sequences are common in 16SrIII phytoplasmas from other hosts and this phytoplasma group is widespread in South America. 16SrIII phytoplasmas highly related are commonly found in Melia azedarach, a widespread tree in Brazil and Argentina. The finding of a new phytoplasma associated with HLB symptoms belonging to the 16SrIII group reinforces the need to develop diagnostic tools to assess HLB-associated microbiomes.